Exploring Learner Autonomy in Online Classes Among Indonesian EFL Students - Noviadayanti, Yossi Rifki (RETAIN, 2021)
Global pandemic has made all school move the teaching-learning process into online. This change come with the demand for students to be more autonomous. The aim of this study is to examine Indonesian high school students’ beliefs on their learner autonomy as well as students’ practices in developing learner autonomy amidst the global pandemic. The subjects of this study were fifteen senior high school students. By employing qualitative design, this study used semi-structured interviews and learning logs as the research instrument. Semi-structured interviews were done to gather data about students’ beliefs on their learner autonomy. Meanwhile, learning logs were filled by the students to obtain data about students’ practices in developing learning autonomy. The findings of this study indicate that, albeit preferring face-to-face learning, the majority of students demonstrate characteristics of autonomous learners such as being able to set learning goals and choosing their learning materials. Furthermore, students show various autonomous learning activities outside their classroom.